(untitled) - Gunderloy, Mike (San Francisco, 2005)
Developer to Designer: GUI Design for the Busy Developer is a unique resource designed to help you and other experienced developers build GUIs for your programs that are simple to learn, easy to use, and painless to maintain, even though you’re not user interface experts. Inside, the focus is on the essentials of Windows and web GUI design: simple ideas that require modest programming effort but provide enormous payoffs in terms of user success and satisfaction.
Giao diện người - máy
Keywords: Graphical user interfaces (Computer systems); Design